2008
DOI: 10.1002/app.28374
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the flame retardant properties of soybean fabric treated with sulphamic acid

Abstract: The effect of sulfamic acid and urea treatments on the flame retardant properties of soybean fabric has been investigated by Limiting Oxygen Index (L.O.I.), Thermogravimetric Analysis (TGA), and X-ray Photoelectron Spectroscopy (XPS) in order to characterize both the bulk and surface properties. The sulfamic acid finish significantly reduced the soybean fabric flammability and appeared to function in the solid phase with increased char formation. Incorporation of urea into the formulation increased the level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
(18 reference statements)
1
13
0
Order By: Relevance
“…A phosphorus-based flame-retardant treatment, Pyrovatex CP, was investigated and found to only Although, the flame-resist performance was marginally lower than that of the sulphamic acid/urea modified soybean, 8 this treatment is cost effective as it does not require any aftertreatment and provides wash-durable flame-retardant fabrics.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A phosphorus-based flame-retardant treatment, Pyrovatex CP, was investigated and found to only Although, the flame-resist performance was marginally lower than that of the sulphamic acid/urea modified soybean, 8 this treatment is cost effective as it does not require any aftertreatment and provides wash-durable flame-retardant fabrics.…”
Section: Discussionmentioning
confidence: 97%
“…6,7 One of the most fundamental technical deficiencies of the fiber is its inherent flammability, affecting the safety of the consumer. In our previous work, 8 we demonstrated that the modification of soybean with sulphamic acid provides flame-retardant properties to the fiber. However, low durability to laundering was observed upon washing.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly in the light of these environmental and commercial factors and the recent advances in the genetic modification of plant proteins there has been renewed interest into regenerated proteins fibers (Vynias et al 2013). In the past decades, protein-based fibers have attracted much attention, not only in academic field, but also in industrial field (Zhu et al 2011;Zhang et al 1999;Zhang et al 2003;Vynias and Carr 2008;Chen et al 2001;Zhang et al 2009). …”
Section: Introductionmentioning
confidence: 98%
“…Nonetheless, as aforementioned, at the end of the twentieth century, there was a growing attention on eco-friendly natural-based sustainable biodegradable fibers due to ecological concerns, which leads to the awakening of promising soybean protein fiber. Key technological developments also provide opportunity for soybean protein fiber production with an ecologically friendly route leading to renewed interest [10][11][12][13]. Soybean cultivation has recently become much more cost-effective and soybean is one of the most abundant agricultural crops [14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, soybean is cheap and abundant [6]. Furthermore, recent technical performance enhancement of soybean protein fiber via geneticengineering techniques extends the commercial scope of this fiber [10,11]. Therefore, in the 2000s, new soybean protein fiber, made from soybean protein and polyvinyl alcohol, was developed and a new soybean fibers' production process commercially promoted, standardized and launched to the textile markets [1].…”
Section: Introductionmentioning
confidence: 99%